Personality profile of amateur team handball referees - Dodt, M.; Fasold, F.; Memmert, D. (German Journal of Exercise and Sport Research, 2023)
Referees play a central role in competitive sport. Particularly in amateur sport, referees contribute significantly to making participation in sport possible for the masses. However, considering that every referee`s career starts at the grassroots level, it is very surprising that there has been no research on the personality traits of amateur referees so far. The current state of research indicates that personality is an essential component of the requirement profile of referees. Personality has been associated with job performance, particularly with regard to resilience and coping with pressure. Personality also affects effective game management in terms of influencing actions in the game in a preventative and proactive manner. This study, therefore, examines the personality profile of amateur handball referees (n = 582) for the first time using the German version of the Big Five Inventory 2 (BFI-2). Current data from German handball referees at the expert level and the German general population were used to compare and discuss the results. Except for lower scores in the domain of extraversion and the facets of sociability and energy level as well as a higher score in the facet of aesthetic sensitivity, amateur referees did not differ significantly from expert referees. In relation to the general population, the results indicate that handball referees, regardless of performance level, have higher scores in assertiveness, emotional stability, and responsibility. Our findings create awareness of personality traits in handball refereeing and illustrate the applied relevance of personality research, e.g., for coaching or recruitment activities.